Does vertical substrate could influence the dietary protein level and zootechnical performance of the Pacific white shrimp Litopenaeus vannamei reared in a biofloc system? - Olier B.S.* (2020)
© 2020, Springer Nature Switzerland AG.The biofloc technology (BFT) system has been gaining more space in the world aquaculture scenario. Nowadays, the demand for information regarding BFT has grown, and new studies have been developed with the aim of increasing the system’s productivity without harming the environment. In the present study, two dietary protein levels were evaluated (30 and 35% crude protein CP) with the addition or absence of a vertical substrate within the culture units. Ninety-six Litopenaeus vannamei shrimp juveniles (3.55 ± 0.26 g) were stocked in 12 tanks (eight per tank) with an operative volume of 18 L. Both water quality parameters and the microbial profile were monitored during the trial along with a proximate composition analysis of the shrimp at the end of the trial (6 weeks). No interaction between substrate and protein level was observed (P < 0.05); however, a higher final weight, a higher specific growth rate, and a lower feed conversion ratio were reached in treatments containing substrate (P < 0.05). The yield, final biomass, and survival values were not different according to the inclusion of the vertical substrate. Regarding the planktonic community, the groups found in higher concentrations occurred in the following order: diatoms (174.75 ind mL−1), rotifers (80 ind mL−1), nematodes (26 ind mL−1), cladocerans (20.5 ind mL−1), and ciliated protozoans (14.25 ind mL−1). With respect to the proximate composition analysis, differences were observed for dry matter and protein contents. The results suggested that the addition of a vertical substrate enabled savings on dietary protein without losses on growth performance and chemical aspects of shrimp reared in a biofloc system.